URGENCE OF IMPLEMENTATION OF THE IMMIGRATION SURVEILLANCE FUNCTION AS A PREVENTIF EFFORTS: CASE STUDIES OF NIGERIANTRAVEL DOCUMENTS EXAMINATION ON THE NAME OF ECHEZONA KINGSLEY OKOLIE - Feni Yuli Triani (Jurnal Ilmiah Kajian Keimigrasian, 2019)
Foreigners surveillance in Indonesia includes the entry and exit of foreigners to and from Indonesian territory and the presence and activities of foreigners in the Indonesian territory. After the foreigner is granted entry permission according to his visa, the surveillance is under Authority of the immigration office whose working area covers the stranger's residence. This surveillance is carried out as a Preventive Effort of the existence and usefulness of Foreigners in the Indonesian territory. This is based on a selective policy that upholds the value of human rights and regulates how foreigners enter the Indonesian territory. then the formulation of the problem to be investigated is (1) How does the function of the Immigration surveillance function as a preventive Efforts? And (2) How does the Function of the Immigration Surveillance function in handling cases of examining the Nigerian Travel Documents on behalf of Echezona Kingsley Okolie ?. Based on the research results obtained that the Immigration Oversight Function plays a role in carrying out preventive measures for immigration. Preventive efforts carried out by the Immigration Surveillance Sub-Directorate in the form of surveillance and exchange of information with other countries and related institutions in the country. In the case study of the Nigerian National Travel Documents Examination on behalf of Echezona Kingsley Okolie, the Immigration surveillance Function, in this case the Field Surveillance, acts as a preventive efforts. In its implementation, Pasal 71 of Undang Undang No. 6 year 2011 states that every Foreigner in the Territory of Indonesia is required to provide all necessary information regarding his and his family's identity. So because in that case, namely in the implementation of Field Surveilance can not show Travel Documents in the form of a Passport or Visa, then the suspect is subject to a Criminal Case Alleged Foreigners who can not show and submit Travel Documents or Stay Permits owned as referred to in Pasal 116 of Undang Undang No. 6 Year 2011 concerning Immigration.